Pattern of failure in IDH mutated, low grade glioma after radiotherapy – Implications for margin reduction. (March 2021) - Jaspers, J.P.M.; Méndez Romero, A.; Wiggenraad, R.; Compter, I.; Eekers, D.B.P.; Nout, R.A.; van den Bent, M.
Graphical abstract: Highlights: The pattern of failure for IDH mutated, grade 2 glioma is predominantly in – field. Pattern of failure in this study is comparable to historic data. A lower percentage of recurrences are covered by a 5 mm expansion of the GTV.